Possible role of proenkephalin in psoriasis. (25th May 2015) - Nagui, N. A.; Ezzat, M. A.; Abdel Raheem, H. M.; Rashed, L. A.; Abozaid, N. A.
Summary: Background: Psoriasis is a common chronic skin disease that can also affect the mucous membranes and joints. It is multifactorial in origin, occurring in genetically predisposed individuals, and triggered by various endogenous and exogenous factors. Proenkephalin (PENK) is an endogenous opioid polypeptide hormone that acts on specific opiate receptors found on nerve and mucosal cells, and on various cells in the immune system. PENK receptors are expressed on skin cells, and their activation can regulate keratinocyte and melanocyte activities. PENK expression has been found to be increased in keratinocytes in psoriatic skin, and together with its inflammatory basis, this suggests that PENK may be regulated by inflammatory stimuli. Aim: To assess the possible role of PENK in the pathogenesis of psoriasis and to assess if it is related to the severity of psoriatic lesions. Methods: Serum and tissue PENK levels were estimated in 20 patients with psoriasis vulgaris, and compared with those of 20 healthy controls (HCs). Results: PENK levels were found to be significantly increased both in serum and in psoriatic lesions in patients compared with HCs. No significant correlation was found between PENK levels and patient age, disease duration or disease severity (Psoriasis Area and Severity Index). Conclusion: Our results support the role of PENK in the aetiopathogenesis of psoriasis, and indicate that giving anti‐PENK drugs in addition to current antipsoriatic therapies might be of value in treating this common chronic skin disease.